The Design of Crude Palm Oil Clarifier - Al-Zuhair, Sulaiman A. S. (1998)
The objective of this research was to study the settling characteristics of crude palm oil (CPO), and use them to design a crude palm oil settler so that to increase the oil recovery , and hence the oil loss in the effluent can be minimized. The apparent viscosity {'1} of CPO after dilution with water was measured and an equation for its behaviour with shear rate (r) and temperature (I') was derived: '1 = 898 exp (19001T)Y-°·61) The equation was used to model CPO settling. Two approaches to determine the design criteria of the CPO settler were followed - conventional solid/liquid analysis, as proposed by Lim (1977), and liquid/liquid analysis . The liquid/liquid analysis underestimated the required settler height by 38-53 %, and the conventional approach by 55-63 %. Finally, a coagulation Jar test was carried out to examine the effects of five coagulants in the oil recovery from the effluent. The results showed that the use of coagulant can reduce oil loss in the clarifier. The recovered oil was 3 % of the plant throughput.